The effect of accelerators towards the cure characteristics and physical properties of thick rubber article / Siti Zulaikha Ibrahim - Ibrahim, Siti Zulaikha (2019)
This research has been carried out to investigate new approach for curing thick rubber article of 20 cm by height using different combination of accelerators. Five batches of natural rubber, SMR L compounds were prepared with different types of accelerators combinations and curing temperature. The accelerators used were Ncyclohexylbenzothiazole- 2-sulphenamide (CBS), diphenyl guanidine (DPG) and zinc diethyl dithiocarbamate (ZDC). The three types of accelerators at different amount and combination for different compound were adjusted according to the state of cure of control sample. The control sample were cured at 140 °C and only CBS was used as single accelerator. The other four samples were prepared using accelerators combination at different curing time, named as UR130, UR120, UR110 and UR100. Compound UR130 and UR120 were cured at 130 °C and 120 °C respectively with the combination of CBS and ZDC combination. Meanwhile, combination of ZDC and DPG were cured at 110 °C (UR110) and 100 °C (UR100)